The horizontal ladder test (HLT) protocol: a novel, optimized, and reliable means of assessing motor coordination in Sus scrofa domesticus - Liu, Xiaobo; Gutierrez, Ana G.; Vega, Arlette; Willms, Joshua O.; Driskill, Jackson; Panthagani, Praneetha; Sanchez, Jordan; Aguilera, Monica; Backus, Brittany; Bailoo, Jeremy D.; Bergeson, Susan E. (Frontiers in Behavioral Neuroscience, 2024)
Pigs can be an important model for preclinical biological research, including neurological diseases such as Alcohol Use Disorder. Such research often involves longitudinal assessment of changes in motor coordination as the disease or disorder progresses. Current motor coordination tests in pigs are derived from behavioural assessments in rodents and lack critical aspects of face and construct validity. While such tests may permit for the comparison of experimental results to rodents, a lack of validation studies of such tests in the pig itself may preclude the drawing of meaningful conclusions. To address this knowledge gap, an apparatus modelled after a horizontally placed ladder and where the height of the rungs could be adjusted was developed. The protocol that was employed within the apparatus mimicked the walk and turn test of the human standardized field sobriety test. Here, five Sinclair miniature pigs were trained to cross the horizontally placed ladder, starting at a rung height of six inches and decreasing to three inches in one-inch increments. It was demonstrated that pigs can reliably learn to cross the ladder, with few errors, under baseline/unimpaired conditions. These animals were then involved in a voluntary consumption of ethanol study where animals were longitudinally evaluated for motor coordination changes at baseline, 2.5%, 5%, 7.5% and 10% ethanol concentrations subsequently to consuming ethanol. Consistent with our predictions, relative to baseline performance, motor incoordination increased as voluntary consumption of escalating concentrations of ethanol increased. Together these data highlight that the horizontal ladder test (HLT) test protocol is a novel, optimized and reliable test for evaluating motor coordination as well as changes in motor coordination in pigs.